Gheranda samhita commentary on the yoga teachings of sage Gheranda - Saraswati, Swami Niranjanananda (Munger Yoga Publications Trust, 2012)
Gheranda Samhita is a classical text describing seven limbs of yoga as taught by Sage Gheranda to his disciple,King Chandakapali.Sage Gheranda outlines a system which can take the serious aspirant from purification of the body to the highest states of samadhi and knowledge of the soul. Distinguishing it from other hatha yoga systems.Sage Gheranda's seven limbs includes the tattwa dharanas (concentration on the elements) and the seamless merging of hatha yoga and tantra by combining mudras,bandhas and pranayamas with mantra,yantra and mandala.The natural flow of this potent process into dhyana and samadhi is beautifully discussed bringing the teachings to a sublime conclusion. The commentary by Swami Niranjanananda Sarawati guides the modern reader through the details of the practices,many of which are complex,rarely described and cryptically expressed by the sage,Comprehensive instructions are given for all techniques,while subtle understanding and insights into the underlying philosophy and purpose are presented with beauty and simplicity. The original Sanskrit verses,with transliteration and translation are included.
Discourses given during the Sannyasa training course held at Ganga Darshan, Munger, 1992
Keywords: Hatha yoga